THE RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH MULTIPLE PRIMARY LUNG CANCERS ACCORDING TO ORENBURG REGIONAL ONCOLOGICAL CLINIC DATA - E. A. Kalinin; M. A. Senchukova; M. N. Vasukov; P. V. Samoilov; S. O. Mitryakov; S. V. Pinchuk (Исследования и практика в медицине, 2019)
Aim. To assess the immediate and long-term results of treating patients with bilateral lung cancer (LC).Patients and methods. Radically operated 5 patients with primary multiple synchronous LC (PMSLC) and 5 patients with primary multiple metachronous LC (PMMLC) were included in the study. Clinical and morphological data, results of instrumental studies, immediate and long-term treatment results were analyzed. Statistical analysis was performed using the Statistica6 software.Results. Tumors corresponding to T1‑T2 prevailed in both groups. At the same time, both in the PMSLC and PMMLC group, only in one case both tumors corresponded to T1–2N0M0, in the others — one or both tumors were with metastases in lymph nodes of the root or mediastinum. In early postoperative period, the number of surgical complications was 10%, somatic — 20%. All complications were successfully treated conservatively. Postoperative mortality was not observed. In PMMLC and PMSLC cases, one-year relapse-free survival (RFS) was 100% and 80%; two-year — 80% and 60%; three-year — 60% and 60%; four-year — 60% and 20%, respectively. The five-year RFS in patients with PMMPC was 40%. One patient with PMSLC was alive without relapse of disease for 4.5 years. Accordingly, one-year overall survival (OS) was 100% and 100%; two-year — 80% and 80%; three-year — 80% and 60%; four-year — 80% and 40%. Five- and six-year OS in patients with PMMLC were 60% and 20%, respectively.Conclusion. The absence of postoperative mortality and low number of postoperative complications indicate the safety of bilateral operations in patients with bilateral LC. Low rates of patients’ 5‑year survival are connected with problems of primary diagnostics and low efficiency of existing algorithms of regular medical checkup of patients with this pathology. To improve long-term results of LC treatment, it is necessary to more actively introduce the modern programs of dynamic observation and complex examination of patients, undergone surgery for LC, using the annual chest CT and fibrobronchoscopy.